2017
DOI: 10.1038/s41598-017-03295-7
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus E7 Alters Host DNA Methylome and Represses HLA-E Expression in Human Keratinocytes

Abstract: Human papillomavirus (HPV) infection distinctly alters methylation patterns in HPV-associated cancer. We have recently reported that HPV E7-dependent promoter hypermethylation leads to downregulation of the chemokine CXCL14 and suppression of antitumor immune responses. To investigate the extent of gene expression dysregulated by HPV E7-induced DNA methylation, we analyzed parallel global gene expression and DNA methylation using normal immortalized keratinocyte lines, NIKS, NIKS-16, NIKS-18, and NIKS-16∆E7. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 57 publications
(81 reference statements)
5
47
0
Order By: Relevance
“…We have shown here that the CXCL14-mediated CD8 + Tcell tumor suppression is reliant on antigen-specific CD8 + T cells. Counterintuitively, it has been well-established that the HPV oncoproteins interfere with MHC-I trafficking and expression on the surface of HPV-infected cells [22,23]. These findings were recapitulated in our mouse model system, as MHC-I (H-2D b ) expression was greatly decreased in MOE/E6E7 cells compared with HPVnegative normal immortalized MOE cells, the parental cell line of MOE/E6E7 cells ( Fig.…”
Section: Cxcl14 Expression Restores Mhc-i Expression On Tumor Cell Susupporting
confidence: 68%
See 1 more Smart Citation
“…We have shown here that the CXCL14-mediated CD8 + Tcell tumor suppression is reliant on antigen-specific CD8 + T cells. Counterintuitively, it has been well-established that the HPV oncoproteins interfere with MHC-I trafficking and expression on the surface of HPV-infected cells [22,23]. These findings were recapitulated in our mouse model system, as MHC-I (H-2D b ) expression was greatly decreased in MOE/E6E7 cells compared with HPVnegative normal immortalized MOE cells, the parental cell line of MOE/E6E7 cells ( Fig.…”
Section: Cxcl14 Expression Restores Mhc-i Expression On Tumor Cell Susupporting
confidence: 68%
“…HPV E5 binds to MHC-I, trapping it in the Golgi apparatus, preventing trafficking to the cell surface [22]. Previous work from our laboratory has shown that all but one (HLA-F) MHC-Iα subunit is repressed in HPV-positive keratinocytes [23]. Furthermore, the MHC-Iα-subunit HLA-E expression is suppressed by E7-mediated promoter methylation.…”
Section: Discussionmentioning
confidence: 98%
“…Large scale sequencing studies as well as analysis of TCGA data have revealed that up to 20% of HNSCCs contain alterations in antigen processing machinery (APM) or downregulation of MHC class I [20,21] . In HPV positive tumors, the latter is thought to be mediated through viral oncoproteins, E5 and E7, which have been shown to downregulate both MHC class I and class II [22][23][24] . Additional studies show that patients with alterations in these pathways had both decreased CD8 T cell infiltration and worse survival outcomes [25,26] , indicating inhibition of antigen presentation may play a key role in head and neck tumor immune escape.…”
Section: Inhibition Of Antigen Processing and Presentation And Immunementioning
confidence: 99%
“…This study also highlights the importance of meticulous and unequivocal histopathological evaluation to precisely define histopathological tumour subtypes. 43 Cicchini et al 44 analysed the global gene expression and DNA methylation profile in human keratinocytes to identify key host factors and pathways altered by HPV-directed DNA methylation. They found that most class I major histocompatibility complex (MHC-I) molecules were transcriptionally downregulated in an E7-dependent manner.…”
Section: Hpv Infection and Cervical Cancermentioning
confidence: 99%
“…Furthermore, HLA-E expression can be restored through treatment with the demethylating agent, 5-aza, which may provide a new therapeutic approach to treat HPV-positive lesions by activating the HLA-E mediated antitumour immune responses of NK and CD8 + T cells. 44 A recent study was conducted in a large Brazilian sample composed by women recruited with the aid of campaigns for…”
Section: Hpv Infection and Cervical Cancermentioning
confidence: 99%